2022
DOI: 10.1002/iid3.644
|View full text |Cite
|
Sign up to set email alerts
|

CHD4 orchestrates the symphony of T and B lymphocytes development and a good mediator in preventing from autoimmune disease

Abstract: Chromodomain helicase DNA binding protein 4 (CHD4) is an ATPase subunit of the nucleosome remodeling and deacetylation complex. It has been implicated in gene transcription, DNA damage repair, maintenance of genome stability, and chromatin assembly. Meanwhile, it is highly related to cell cycle progression and the proceeding of malignancy. Most of the previous studies were focused on the function of CHD4 with tumor cells, cancer stem cells, and cancer cells multidrug resistance. Recently, some researchers have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…The ATP-dependent chromatin remodeler proteins are implicated in many developmental disorders, including hearing loss [ 2 , 3 ]. Normal CHD4 activity was found to be essential for maintaining stem cell pluripotency [ 4 ], differentiation capacity towards neuronal lineage [ 5 ], T cell development and hematopoietic stem cell [ 6 , 7 ], cardiac development [ 8 , 9 ], renal progenitor cell self-renewal, and differentiation [ 10 ]. It has also been shown that CHD4 can regulate gene expression for maintaining a distinct cellular state and pledge for accurate cell fate decisions upon developmental/external cues [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ATP-dependent chromatin remodeler proteins are implicated in many developmental disorders, including hearing loss [ 2 , 3 ]. Normal CHD4 activity was found to be essential for maintaining stem cell pluripotency [ 4 ], differentiation capacity towards neuronal lineage [ 5 ], T cell development and hematopoietic stem cell [ 6 , 7 ], cardiac development [ 8 , 9 ], renal progenitor cell self-renewal, and differentiation [ 10 ]. It has also been shown that CHD4 can regulate gene expression for maintaining a distinct cellular state and pledge for accurate cell fate decisions upon developmental/external cues [ 11 ].…”
Section: Introductionmentioning
confidence: 99%